Klemens Aleksandryjski, "Kobierce" VII 16, 94, 5: „ἡ ψυχική εὐτονία” i jej znaczenie dla „ὁ τῆς ἀληθείας ἐραστής” – kilka uwag filologicznych - Sus, Grzegorz (Vox Patrum, 2025)
The article analyzes an enigmatic sentence from Book Seven of the Stromata by Clement of Alexandria: “I think that the lover of truth needs a psychikē eutonia”. The Author examines two key questions: who is the “lover of truth”, and what does the term psychikē eutonia mean? The article is divided into seven sections and employs both philological analysis and historical-comparative interpretation. Clement redefines the notions of both truth and the lover of truth (in contrast with the Platonic doctrine). Truth is no longer a metaphysical idea but Christ himself; and the lover of truth is no longer the philosopher, but the Christian gnostic striving for union with God through knowledge, discipline, and prayer. Eutonia refers to a state connected with inner tension (tonos), which enables mastery over passions and supports the path toward true gnosis. The primary sources include Clement’s Stromata, Platonic dialogues, and fragments of Stoic and Middle Platonic writings. The aim of the author is to propose possible interpretative paths for the problematic sentence.